Factors impact on state management about youth in current situation - Vũ Minh Thái (Tạp chí Nghiên cứu Khoa học Công đoàn, 2023)
The analysis results show that there are 5 factors that directly affect the state management of youth in the current situation, specifically (1) The leadership of the Communist Party of Vietnam; (2) The management of the state management agency; (3) Impact of market mechanism; (4) The response and support of the whole society and (5) Youth participation in youth work. In order to effectively implement the state management of youth in our country, it is necessary to have the participation and synchronous implementation of the whole political system, social organizations, families, and the youth themselves - the main subjects of this policy on state management of youth.